Extensive Microbial Processing of Polysaccharides in the South Pacific Gyre via Selfish Uptake and Extracellular Hydrolysis - Reintjes, Greta; Fuchs, Bernhard M.; Amann, Rudolf; Arnosti, Carol (Frontiers in Microbiology, 2020)
Primary productivity occurs throughout the deep euphotic zone of the oligotrophic South Pacific Gyre (SPG), fueled largely by the regeneration of nutrients and thus recycling of organic matter. We investigated the capabilities of heterotrophic bacterial communities to process polysaccharides, important high molecular weight (HMW) components of marine organic matter, at three sites in the SPG. We focused on the initial step of HMW organic matter degradation by measuring the activities of extracellular enzymes that hydrolyze six different polysaccharides to smaller sizes. This process can occur by two distinct mechanisms: ‘selfish uptake’, in which initial hydrolysis is coupled to transport of large polysaccharide fragments into the periplasmic space of bacteria, with little to no loss of hydrolysis products to the external environment, and ‘external hydrolysis’, in which low molecular weight hydrolysis products are produced in the external environment. To our surprise, all six polysaccharides were hydrolyzed externally and taken up selfishly in the center of the gyre, observations that may be linked to a comparatively high abundance of diatoms at the depth and location sampled (75 m). At the edge of the gyre and close to the center of the gyre, four of six polysaccharides were externally hydrolyzed, and a lower fraction of the bacterial community showed selfish uptake. One polysaccharide (fucoidan) was selfishly taken up without measurable external hydrolysis at two stations. Additional incubations of central gyre water from depths of 1250 and 2800 m with laminarin (an abundant polysaccharide in the ocean) led to extreme growth of opportunistic bacteria (Alteromonas), as tracked by cell counts and next generation sequencing of the bacterial communities. These Alteromonas appear to concurrently selfishly take up laminarin and release low molecular weight hydrolysis products. Overall, extracellular enzyme activities in the SPG were remarkably high, and a considerable fraction of the community was capable of selfish uptake at all three stations. A variety of bacteria are capable of cycling HMW organic matter using distinct polysaccharide processing mechanisms in the SPG.